Geography of the Production Circuit of Illicit Psychoactive Substances (IPS). Globalization, Actors and Multiscalarity - Pyszczek, Óscar-Luis (2021)
The production, trafficking and consumption of illicit psychoactive substances (IPS) constitute, at the dawn of the 21st century, a phenomenon and a problem of global scope and implications with solutions that are not yet found. Investigating the productive circuit of CPS is a complex, multidimensional and markedly multiscalar and multiterritorial issue. The main objective of this article is to show the spatial and temporal multiscalarity of the CPS circuit, determining the relational flow between the global and the local. Quantitative and qualitative sources are used, both primary and secondary, to illustrate integrally its causes, its state and its effects at a glocal level. The results, from the approach of global studies, reveal the spaces where different stages of this illicit activity are carried out. The investigation evidences the economic, social and political relations involved in a complex and multifaceted phenomenon, as well as the multiscale dynamics of it.